2016
DOI: 10.3389/fpsyg.2016.01335
|View full text |Cite
|
Sign up to set email alerts
|

Cue Reactivity in Nicotine and Alcohol Addiction: A Cross-Cultural View

Abstract: A wealth of research indicates that cue reactivity is critical to understanding the neurobiology of nicotine and alcohol addiction and developing treatments. Functional magnetic resonance imaging (fMRI) and electroencephalograph (EEG) studies have shown abnormal cue reactivity in various conditions between nicotine or alcohol addicts and the healthy. Although the causes of these abnormalities are still unclear, cultural effect can not be ignored. We conduct an review of fMRI and EEG studies about the cue react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(8 citation statements)
references
References 100 publications
1
7
0
Order By: Relevance
“…Our recent study that used resting state functional magnetic resonance imaging (rsfMRI) to study love-related changes in resting state functional connectivity provided some new and important evidences for romantic love related functional alterations in brain network (Song et al, 2015 ). Combined our previous studies about romantic love (Wang et al, 2016 ) and addiction (Zhang et al, 2009 , 2011 ; Lv et al, 2016 ; Wei et al, 2016 ), we found that romantic love and addiction have the significant differences in resting-state brain network. Therefore, systematic comparison between romantic love and addiction may be helpful to understand the similarities and differences of them, and may inspire a new possible treatment to addiction.…”
Section: Introductionsupporting
confidence: 77%
“…Our recent study that used resting state functional magnetic resonance imaging (rsfMRI) to study love-related changes in resting state functional connectivity provided some new and important evidences for romantic love related functional alterations in brain network (Song et al, 2015 ). Combined our previous studies about romantic love (Wang et al, 2016 ) and addiction (Zhang et al, 2009 , 2011 ; Lv et al, 2016 ; Wei et al, 2016 ), we found that romantic love and addiction have the significant differences in resting-state brain network. Therefore, systematic comparison between romantic love and addiction may be helpful to understand the similarities and differences of them, and may inspire a new possible treatment to addiction.…”
Section: Introductionsupporting
confidence: 77%
“…Most of the studies focus their attentions on neuroimaging effects of alcohol cue exposure. 3 5 In this process, neuroimaging methods were widely used to demonstrate task-specific or cue-specific alterations in regional brain activity. However, it may hamper us to insights into integrated global brain function alterations in resting-state or non-task condition when we solely focus on regional functional brain activity alterations under task-specific or cue-specific conditions because of the behavioral variability.…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has shown that co-use of alcohol and tobacco is associated with significantly greater demand for alcohol compared with use of alcohol alone, even after controlling for differences in drinking and demographics (Amlung et al 2017;Yu rasek et al 2013). This difference is hypothesized to result from several factors including cross-commodity craving and cue reactivity, as well as alcohol priming (Drobes, 2002;Lv et al, 2016;McKee et al, 2010).…”
mentioning
confidence: 99%